What Role Does Cyberloafing Play in Disengaging Civil Servants in West Aceh Regency? - Mariadita, Icha; Rusdi, Rusdi; Hidayat , Muhammad Rahmat; Muzakir, Muzakir; Fajri, Ikhsan (Jurnal Transformasi Administrasi, 2024)
This study investigates the interrelationships among various latent variables and theirobserved indicators using a structural equation model (SEM). The findings reveal that sharing,shopping, and real-time updating activities positively impact job-related outcomes, suggestingthat moderate engagement in these activities can mitigate employee disengagement.Conversely, accessing online content shows a slight negative influence on job performance,highlighting the potential detriments of cyberloafing. The study also underscores thesignificant positive impact of organizational support and supervisory evaluations on jobperformance. Integrating theories of cyberloafing and employee disengagement, the resultssuggest that fostering a supportive work environment and allowing for healthy, non-workrelated activities can enhance job satisfaction and reduce counterproductive behaviors. Theimplications of these findings are critical for designing interventions and policies that promotepositive engagement and minimize the risks associated with cyberloafing, ultimately enhancingoverall employee performance and satisfaction.